Contributions to the knowledge of predaceous midges of the subgenus Eukraiohelea Ingram & Macfie of Stilobezzia Kieffer (Diptera: Ceratopogonidae), from Brazil - Cazorla, Carla Gisela (2017)
Two new species of predaceous midges of the subgenus Eukraiohelea Ingram & Macfie of Stilobezzia Kieffer are described and illustrated: Stilobezzia (Eukraiohelea) proxima n. sp. and S. (E.) quasielegantula n. sp. The previously known New World species, Stilobezzia (E.) elegantula (Johannsen) is redescribed and illustrated. The species are illustrated through photomicrographs from adult males and females collected in the Brazilian state of Rio de Janeiro. A key to adults of the five American species of Stilobezzia (Eukraiohelea) is also provided.